2018
DOI: 10.1016/j.htct.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diarrhea in autologous stem cell transplantation: high prevalence of coccidia in a South American center

Abstract: BackgroundDiarrhea is frequently seen in autologous stem cell transplantation. Although toxicity related to conditioning is the most common cause, infectious pathogens can play a distinctive role particularly in certain regions and environments.MethodsThe role of enteropathogens was investigated in 47 patients submitted to autologous stem cell transplantation at a Brazilian center between May 2011 and May 2013. All patients who presented with diarrhea consented to stool sample analysis to identify the etiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In developing countries without good hygienic foundations, parasitic infections are common but there is usually no routine screening of MM patients. In a recent report from Brazil, de Castro et al [ 2 ] studied infectious diarrhea in autologous stem cell transplantation cases, including myeloma patients, and found that there were many parasitic infections including C. belli infections. In conclusion, we suggest a new recommendation for screening for parasitic infection in any patients with MM and other hematological malignancies.…”
Section: To the Editormentioning
confidence: 99%
“…In developing countries without good hygienic foundations, parasitic infections are common but there is usually no routine screening of MM patients. In a recent report from Brazil, de Castro et al [ 2 ] studied infectious diarrhea in autologous stem cell transplantation cases, including myeloma patients, and found that there were many parasitic infections including C. belli infections. In conclusion, we suggest a new recommendation for screening for parasitic infection in any patients with MM and other hematological malignancies.…”
Section: To the Editormentioning
confidence: 99%
“…In this issue of Hematology, Transfusion and Cell Therapy, Castro et al investigated the role of enteric pathogens in 47 recipients of ASCT between May 2011 and May 2013. 7 Thirty-nine recipients (83%) met the criteria for the diagnosis of diarrhea. Among them, conditioning regime toxicity was the most prevalent cause (35%).…”
mentioning
confidence: 99%